Finite-Element Analysis of the Effect of Utilizing Various Material Assemblies in “All on Four” on the Stresses on Mandible Bone and Prosthetic Parts - Yomna H. Shash; Mohamed T. El-Wakad; Mohamed A. A. Eldosoky; Mohamed M. Dohiem (International Journal of Polymer Science)
Background. Fixed prostheses often utilize the “All-on-four” technique, in which four implants are inserted into the jaw bone, and a framework supports them. Titanium is usually used in the fabrication of “All-on-four” parts, due to its superior mechanical properties; however, it has drawbacks such as aesthetic impairment, casting issues, stress shielding, and incompatibility with imaging techniques. These drawbacks have motivated researchers to find alternative materials such as polymers. Recently, the new polymeric material PEEK has a major role in most areas of dentistry, and therefore, it can represent an alternative biomaterial to overcome the drawbacks of titanium. The density of bone is expected to influence the choice of “All-on-four” materials. Purpose. This research applied finite-element investigations to evaluate the stresses on bone tissues and prosthetic parts in “All on four,” utilizing three assemblies of materials, in normal and low bone densities. These assemblies were titanium (Type 1), titanium/PEEK (Type 2), and PEEK (Type 3). Materials and Methods. A 3D Mandibular model was constructed with a fixed prosthesis, and three assemblies of materials were stimulated, under 300 N unilateral force. The von Mises stresses were computed for the prosthetic parts and mucosa, while the maximum and minimum principal stresses/strains were computed for bone tissues due to their brittle and ductile properties. Moreover, the displacements of implants were extracted to check the prosthesis stability. Results. Type 2 and Type 3 minimized the stresses on frameworks, implants, abutments, and bone tissues, however, increased the mucosal stress, in comparison to Type 1. In the low-density model, Type 3 was recommended to reduce the stresses/strains on bone tissues and decrease the implant displacement, avoiding bone failure and increasing prosthesis stability. Conclusions. The bone density influenced the choice of “All-on-four” assembly. Moreover, further research on PEEK implants and abutments is required in the future.